Study on the Fabrication and Acoustic Properties of Near-Stoichiometric Lithium Tantalate Crystal Surface Acoustic Wave Filters - Jiashun Si; Xuefeng Xiao; Yan Huang; Yan Zhang; Shuaijie Liang; Qingyan Xu; Huan Zhang; Lingling Ma; Cui Yang; Xuefeng Zhang (Crystals, 2024)
Near-stoichiometric lithium tantalate (NSLT) wafers with different Li contents were prepared by vapour transfer equilibrium (VTE) method and fabricated into surface acoustic wave filters. The temperature coefficient of frequency, insertion loss, and bandwidth of the surface acoustic wave filters were tested using a special chip test bench and a network analyzer. The results show that the temperature coefficient of frequency shows a trend of first decreasing and then increasing with the increase in Li content, and the temperature stability of the surface acoustic wave filters is best when the Li content is 49.75%. It is also found that the surface acoustic wave filter fabricated from NSLT wafers has 21.18% lower temperature coefficient of frequency, 7.3% lower insertion loss, and 2.8% lower bandwidth than those fabricated from congruent lithium tantalate wafers. Therefore, NSLT crystals are more suitable for applications in acoustic devices, providing a new idea for performance enhancement of 5G communication devices.